Increased All-cause Mortality in People With HIV and Comorbidities: Hepatitis B and C Virus Seropositivity and Hyperglycemia in Myanmar, 2005–2017. (13th December 2022) - Kyaw, Nang Thu Thu; Satyanarayana, Srinath; Harries, Anthony D; Kumar, Ajay M V; Kyaw, Khine Wut Yee; Phyo, Khaing Hnin; Hayat, Matthew J; Castro, Kenneth G; Magee, Matthew J
Abstract: Background: Hepatitis C virus (HCV) and hepatitis B virus (HBV) coinfection are associated with increased mortality in people with HIV (PWH), and hyperglycemia is a common comorbidity in PWH. In this study, we used routinely collected clinical data to assess the associations between HBV and HCV seropositivity with all-cause mortality and whether this relationship differs by hyperglycemia status. Methods: Eligible participants included adult PWH (≥15 years) who initiated antiretroviral therapy between May 2005 and June 2016 in Myanmar. HBV and HCV serostatus and hyperglycemia were measured at enrollment to HIV care using HBV surface antigen, HCV antibody tests, and random blood glucose (≥140 mg/dL), respectively. Results: Among 27 722 PWH, 2260 (8%) were HBV seropositive, 2265 (9%) were HCV seropositive, 178 (0.6%) were HBV-HCV seropositive, and 1425 (5%) had hyperglycemia. During the median follow-up (interquartile range) of 3.1 (1.5–5.1) years, 3655 (13%) PWH died, and the overall mortality rate was 3.8 (95% CI, 3.7–3.9) per 100-person-years (PY). The mortality rate (per 100 PY) among PWH who were HBV seropositive was 4.6, among PWH who were HCV seropositive it was 5.1, and among PWH who were HBV-HCV seropositive it was 7.1. When stratified by glycemic status, the mortality rate was higher among patients with hyperglycemia compared with those with euglycemia (5.4 vs 4.0 per 100 PY), and the difference in mortality rate between patients with hyperglycemia and euglycemia was highest among those with HCV seropositivity (9.8 vs 5.0 per 100 PY). Conclusions: Increased mortality rates associated with HBV and HCV seropositivity in PWH differed by their glycemic status. PWH with HCV seropositivity and hyperglycemia had the highest mortality rates.